THE IMPORTANCE OF THE DELIVERY OF WRITTEN DOCUMENTS FOR A MISDEMEANOR PROCEDURE - Jeličić, Mladen (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
The author discusses different aspects of the delivery of written documents in the misdemeanor proceedings. After the introduction and consideration of the characteristics of this term, it is pointed out on its substantive aspect, which is reflected in the delivery of the written documents as an important feature of certain misdemeanors. The procedural aspect of delivery is manifested in several modalities. The author analyzed briefly the manner of delivering the written documents in accordance with the provisions of the Law on Misdemeanors, while special attention was paid to the relation of delivering written documents and the rights of the defendant to the defense. It was emphasized that this procedural action is the condition for the application of certain procedural institutes and it is indicated on the specificity of the delivery of the documents in case of issuing a misdemeanor order, with a reference to the executive misdemeanor procedure. The author points to the consequences of unlawful delivery. The author’s conclusion is that the delivery of the written documents is the condition of a fair misdemeanor procedure and that in practice, special attention to the lawful treatment must be paid. The work is corroborated by the rich case law of various judicial instances.